ANALISIS KEBIJAKAN JAMINAN KESEHATAN KOTA BENGKULU DALAM UPAYA EFISIENSI DAN EFEKTIFITAS PELAYANAN DI PUSKESMAS - Yandrizal Yandrizal; Betri Anita Anita; Desri Suryani (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background. Mayor of Bengkulu Regulation Number 13 Year2012 on The Implementation Guidelines for State HealthInsurance Assistance Costs (Jamkeskot) in Bengkulu city ismanaged by the Secretariate of the Government of CommunityWelfare Section in Bengkulu. The cost of referral health carein Provincial General Hospital could be made more efficient byoptimizing the role of community health centers as a curative,preventive and promotive health services. It is hoped to reducethe number of visits for treatment and referral to hospital. Thepurpose of this study is to analyze the City Health Insurancepolicies in an effort to improve the efficiency and effectivenessof primary health care and public health efforts to reduce thenumber of visits for treatment and referral to hospital.Method: The type of research is non-experimental research,or also called qualitative research. It is an exploratory researchto find a new role of the city government and AdministeringAgency to improve the efficiency and effectiveness of healthservices at the health center.Unit of Analysis: 1) Community Health Center Unit 20, 2)organizing: PT. Askes 2 person and Community Welfare section2 person, 3) the City: Head of the Community Welfare Section1 person, Bengkulu City Health Office 2 person. Data is collectedusing interview using questionnaire as the instrument, anddocuments review.Results: Bengkulu Jamkeskot policies have not applied theprinciple of insurance in which the organizers serves to controlthe quality and cost of health care provided in both basicservices/primary and referral services. Most of the healthcenters tend to refer patients (67%) that are still within theirauthorization to provide care. The reason being: the healthcenters have limited equipment and drugs, and some patientsdemanded to be referred due to perceived bad quality of serviceat the health centers. The Community Welfare section has notcoordinated with the City Health Office to conduct training forthe health center in an effort to increase the effectiveness ofservices.Recommendation: The City Government is to establish ateam to conduct technical guidance supervision to healthcenters to ensure that the health centers play the role ofgatekeeper and only refer patients that need complex care,providing medical equipment and drugs to the health centerswith proposed funding from Bengkulu City budget and provincialbudget. The Health Centers are to provide routine counselingon healthy behavior and IEC on nutrition and hygiene to everyposyandu. The City Health Office provides technical guidancein drafting POA for promotive and preventive activities to havemore focus in efforts to control the causes of disease. Improvepolicy management of Jamkeskot by submitting the managementto an administering body, so that the Jamkeskot can apply theinsurance principles where the strong help the weak, thehealthy help the sick, the rich help the poor; and also cancontrol the quality and cost of service.Keywords: Health Policy, Health Insurance, Gatekeeper